Expression of Interleukin (IL)-10, IL-17A and IL-22 in Serum and Sputum of Stable Chronic Obstructive Pulmonary Disease Patients. (1st August 2013) - Zhang, Li; Cheng, Zhenshun; Liu, Weimin; Wu, Kaisong
Abstract: Interleukin (IL)-17A, IL-22 and IL-10 have been implicated in the development of chronic obstructive pulmonary disease (COPD), but their expression in COPD is uncertain. Here we investigate the expression of IL-17A, IL-22 and IL-10 in the serum and sputum of COPD patients. Blood samples and induced sputum samples were collected from 94 patients with COPD, 23 healthy smokers, and 22 healthy control non-smokers. IL-17A, IL-22 and IL-10 were measured by enzyme-linked immunosorbent assay (ELISA). We found that: 1) serum and sputum IL-17A were higher in COPD compared to healthy smokers and non-smokers; 2) serum IL-17A increased with COPD stages, it was inversely correlated with percentage of forced expiratory volume in the first second (FEV1 %) reference and positively correlated with C-reactive protein (CRP), Sputum IL-17A levels in the severe COPD patients were positively correlated with sputum neutrophils, and reversely correlated with sputum macraphages ( p < 0.01); 3) serum and sputum IL-22 were significantly higher in COPD and healthy smokers than those in the non-smoker group, sputum IL-22 was similar in severe COPD (stage III and IV), which were higher than those in the other groups ( p < 0.05); and, 4) serum and sputum IL-10 were similiar in COPD and healthy smokers, which were decreased compared to non-smokers. These data suggest that the increased level of IL-17A in serum and sputum plays important roles in the pathogenesis of COPD. The increased sputum IL-22 might also play important roles in the pathogenesis of COPD, while IL-10 secretion might be not only affected by COPD but also by cigarette smoke.